Morphometric Relationship of the Transverse Sinus with Sigmoid Sinus Groove and Jugular Foramen - Rijal, Suman; Nepal, Pankaj Raj; Bishokarma, Suresh; Ranabhat, Kajan; Gongal, Dinesh Nath (Nepal Journal of Neuroscience, 2018)
Cranial venous sinus anatomy is fundamental in neurosurgery and radiology, especially in surgical planning and treatment of neurological diseases. In this study, we aimed to study the morphometric relationship of the transverse sinus with sigmoid sinus groove and jugular foramen and imply if this relationship could aid in diagnosing the transverse sinus thrombosis. This is a retrospective analytical study conducted in our center among 30 patients who underwent Computed Tomography (CT) venogram during a period of 1 year. Diameter of transverse sinus and sigmoid groove at midpoint, and diameter of jugular foramen as it enters the skull base were collected. Relation of transverse sinus with sigmoid sinus groove and jugular foramen was analyzed. There were 60 transverse sinuses in the study with left and right being 50% (30 each). Mean age of patients collected was 53.20 years. There were 43.3% male and 56.7% female patients. Diameter of the Transverse sinus has statistically significantly linear relationship with the diameter of the sigmoid sinus groove and jugular foramen (p<0.001) and was positively correlated (r= 0.651 and 0.624 respectively). Diameter of the transverse sinus has significant positive linear correlation with the sigmoid sinus groove and jugular foramen.